A MANAGEMENT OF PLACENTAL RETENTION IN BALINESE CATTLE IN SOREANG VILLAGE, MAPPAKASUNGGU SUB-DISTRICT, TAKALAR REGENCY: PENANGANAN RETENSI PLASENTA PADA SAPI BALI DI DESA SOREANG KECAMATAN MAPPAKASUNGGU KABUPATEN TAKALAR - Dwi Arini Ardat Ardat; Kadek Dian Krisna Putri; Fika Yuliza Purba; Nur Alif Bahmid (Hasanuddin University, 2026)
The livestock sector is one of the most developed sectors by the Indonesian people, including the people in Takalar Regency. One of the reproductive disorders in livestock that is often found in Takalar Regency is placenta retention. This disease has a fairly clear sign that some of the fetal membranes hang out of the vulva 12 hours or more after normal partus, abortion or dystocia. On 18 May 2024, Dg. Tole, the owner of a five-year-old female Balinese cow from Soreang Village, Mappakasunggu Subdistrict, Takalar District, reported the condition of his cow where 24 hours after giving birth the placenta of the cow had not come out. The cow had a Body Condition Score (BCS) of 3/5 and gave birth to a Brahman bull calf. The methods of diagnosis were history taking, signalling and physical examination. The results of the physical examination found mucus mixed with blood coming out of the vagina and on intravaginal palpation examination found cotyledons and carancula still attached in the uterus. The cow was diagnosed with placental retention due to dystocia. Treatment was carried out by manual removal and administration of antibiotics, anti-inflammatory drugs, and supportive therapy.